2007
DOI: 10.1007/s11524-007-9215-1
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Social Network Influence among Injection Drug Users: Perceived Norms and Needle Sharing

Abstract: Whereas substantial research has linked perceived norms and HIV sexual risk behavior, less attention has been given to the relationship between perceived norms and injection drug practices. This study investigated the relationship between needle sharing and perceived norms in a sample of injection drug users. Data were collected through face-to-face interviews with 684 injectors from the STEP Into Action (STEP) project in Baltimore, Maryland. Logistic regression was used to assess the associations between perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 35 publications
4
43
0
Order By: Relevance
“…Since all data on network members is provided by the participant (i.e., by proxy), this finding suggests that the perceived HCV status of one's partner may be an important predictor of risk behaviors within young PWID partnerships as previously reported (Hahn et al, 2010). Consistent with much past research (Davey-Rothwell and Latkin, 2007; Gollub et al, 1998; Latkin et al, 1998a; Miller and Neaigus, 2001; Tracy et al, 2014), women were more likely to share syringes with male partners, many of whom are also sex partners, after adjusting for participant and network characteristics (Table 4). Gender-specific interventions for PWID are needed to address this overlap in the sexual- and drug-using networks among women that enhances risk for HIV and other infections.…”
Section: Discussionsupporting
confidence: 82%
“…Since all data on network members is provided by the participant (i.e., by proxy), this finding suggests that the perceived HCV status of one's partner may be an important predictor of risk behaviors within young PWID partnerships as previously reported (Hahn et al, 2010). Consistent with much past research (Davey-Rothwell and Latkin, 2007; Gollub et al, 1998; Latkin et al, 1998a; Miller and Neaigus, 2001; Tracy et al, 2014), women were more likely to share syringes with male partners, many of whom are also sex partners, after adjusting for participant and network characteristics (Table 4). Gender-specific interventions for PWID are needed to address this overlap in the sexual- and drug-using networks among women that enhances risk for HIV and other infections.…”
Section: Discussionsupporting
confidence: 82%
“…Perceived norms have been generally categorized as descriptive or injunctive. Descriptive norms indicate the perceived prevalence of a behavior in a group, whereas injunctive norms refer to perceived approval or disapproval of a behavior (Davey-Rothwell and Latkin, 2007). Empirical examination of these two constructs has also revealed that their significance in determining a behavior varies based on the context and specific behavior (Reno et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Social norms are, for that reason, inherently linked to an individual's social networks because they usually materialize out of interactions with others and how deviations are sanctioned by network members (Cialdini and Trost, 1998). Although there is a growing literature examining network features of norms among vulnerable populations other than homeless youth (Davey-Rothwell and Latkin, 2007; Latkin et al, 2003, 2010), very few studies have examined associations between social network structural characteristics (such as network position and cohesiveness) and normative perceptions of risk behaviors, such as substance use. To our knowledge, no study has explored the intersection of social network structure and substance use norms in the homeless youth population.…”
Section: Introductionmentioning
confidence: 99%
“…Our sample was comprised of male PWIDs who were enrolled as part of a broader investigation of the social network factors associated with HIV risk among male clients of FSWs, therefore our findings may not generalize to other PWIDs who are not engaged in commercial sex or to female drug users. Other social network based research has found that social network norms related to syringe sharing have different effects for men and women [55]. The authors suggest that the differential effect of social norms for syringe sharing may signal the presence of other influential members of the social network, or could mean that women are less compelled to gain approval or acceptance through compliance with some types of norms.…”
Section: Limitationsmentioning
confidence: 99%